Busy bunny days ebook In the town, on the farm & at the port. - Teckentrup, Britta (2023)
Follow the Bunny family’s adventures in this seek-and-find book: “A treasure trove for kids who love a visual challenge.” — Booklist   Join the Bunny family for a busy day in their hometown, on a fun-filled farm adventure, and at the port for an exciting outing in this seek-and-find book where there is always something to discover. From the time they wake up until the time they go to sleep, there is so much to see and do. Don’t forget to keep an eye out for that pesky Benny Badger—he is always up to no good!   With a fresh and adorable illustration style, and so many details on every page, this picture book begs to be read again and again—and invites kids to create their own stories about the bunnies’ travels and the numerous places and characters.   “Reminiscent of Richard Scarry’s Busytown books, Martin Handford’s Where’s Waldo? series, and Jean Marzollo’s I Spy series, the book will captivate the same audience with its inviting, intricate illustrations.” — Booklist   “Children are going to love exploring the artwork in this wonderful picture book.” — Through the Looking Glass